Serum Levels of Total IgE, IL-12, IL-13 and IL-18 in Children Patients with Asthma - M. Saleh Al-Quraishi, Ghadah (Iraqi Journal of Pharmaceutical Sciences, 2017)
T-cell activation and alteration of cytokine levels are involved in the pathogenesis of asthma. However, the profile of circulating T-lymphocyte subsets and related cytokines during asthmatic attacks is still unclear. We compared the serum concentrations of proinflammatory cytokines Interleukine-18( IL-18) and Interleukine-12(IL-12), T-helper 2 (Th2) cytokine Interleukine-13(IL-13 ) and Immunoglobuline-E ( IgE) in 27 asthmatic children and 21 sex and age matched healthy control subjects. Serum cytokines and IgE concentrations were measured by enzyme-linked immunosorbent assay. Serum IL-13 , IL-18 and IgE concentrations were significantly higher in asthmatic patients than normal control subjects ( IL-13: median 9.73 versus 4.43 pg/ml, P<0.05 ; IL-18: 76.81 versus 35.41 pg/ml, P<0.05 ; IgE: 225.44 versus 37.94 IU/ml, P<0.05 . Asthmatic patients showed a decreased serum IL-12 concentration 93.57 versus 122.83 pg/ml, P<0.05 . In conclusion, it was suggested that IL-13 and IL-18 might have a potential role in controling lymphocyte responses in asthmatic patients specially in children through an IgE-mediated pathway.Key words: Asthma, Interleukine-12, -13, -18, Immunoglobuline-E.